Building sustainable potato enterprises in Cameroon. Project profile - International Potato Center (International Potato Center, 2019)
In Cameroon, potato is viewed as a useful food security and cash crop, but farmers face multiple productivity constraints. This project aims to increase food security, nutrition and incomes by improving farmers’ access to quality planting materials and training stakeholders on sustainable production, seed multiplication and marketing within an overall national potato strategy.